Wonder and the marvellous from Homer to the Hellenistic world - Lightfoot, Jessica, 1991- (Cambridge classical studies., 2021)
Wonder and wonders constituted a central theme in ancient Greek culture. In this book, Jessica Lightfoot provides the first full-length examination of its significance from Homer to the Hellenistic period. She demonstrates that wonder was an important term of aesthetic response and occupied a central position in concepts of what philosophy and literature are and do. She also argues that it became a means of expressing the manner in which the realms of the human and the divine interrelate with one another; and that it was central to the articulation of the ways in which the relationships between self and other, near and far, and familiar and unfamiliar were conceived. The book provides a much-needed starting point for re-assessments of the impact of wonder as a literary critical and cultural concept both in antiquity and in later periods.